(3x+5)(5x+3)=

Simple and best practice solution for (3x+5)(5x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+5)(5x+3)= equation:


Simplifying
(3x + 5)(5x + 3) = 0

Reorder the terms:
(5 + 3x)(5x + 3) = 0

Reorder the terms:
(5 + 3x)(3 + 5x) = 0

Multiply (5 + 3x) * (3 + 5x)
(5(3 + 5x) + 3x * (3 + 5x)) = 0
((3 * 5 + 5x * 5) + 3x * (3 + 5x)) = 0
((15 + 25x) + 3x * (3 + 5x)) = 0
(15 + 25x + (3 * 3x + 5x * 3x)) = 0
(15 + 25x + (9x + 15x2)) = 0

Combine like terms: 25x + 9x = 34x
(15 + 34x + 15x2) = 0

Solving
15 + 34x + 15x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(5 + 3x)(3 + 5x) = 0

Subproblem 1

Set the factor '(5 + 3x)' equal to zero and attempt to solve: Simplifying 5 + 3x = 0 Solving 5 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 0 + -5 3x = 0 + -5 Combine like terms: 0 + -5 = -5 3x = -5 Divide each side by '3'. x = -1.666666667 Simplifying x = -1.666666667

Subproblem 2

Set the factor '(3 + 5x)' equal to zero and attempt to solve: Simplifying 3 + 5x = 0 Solving 3 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = 0 + -3 5x = 0 + -3 Combine like terms: 0 + -3 = -3 5x = -3 Divide each side by '5'. x = -0.6 Simplifying x = -0.6

Solution

x = {-1.666666667, -0.6}

See similar equations:

| 5+2h=10+.50h | | 10.7-56= | | .5a+1=9 | | 10a-17=13 | | 10.7-5= | | -j+5=19 | | 7+x=17.1 | | (x+3)(x-y)=z^2+x^2 | | -3x+5x-11=2(x-4)-35 | | 21-9y+2y=7 | | 10y(2.5+2)+3x=5(3-x) | | 7z+13=16z+8 | | 10y+4=54 | | 10x^2-15x+7=0 | | 4v/27=16*27 | | -13=8x+11 | | 2/3h=28 | | 10m+5=12m-28 | | b/5.4=-3 | | -23(-2)=x | | 5x+4(x-13)=5(x-8) | | V(2v-1)=0 | | 4y(2y-3x)-2x(x-3y)= | | (-9)[3+3]-12= | | 8n+16.2=1.825 | | 22.5+7.5= | | 3/2(x-5)=/6 | | x(3x-5)=(3x+6)(x-3) | | 6(x-8)=12(x+4) | | 3n+5n+2+n= | | (4q+9)(4q+9)=0 | | 4(x+3)=2x+10+2x |

Equations solver categories